PENINGKATAN KEMAMPUAN JOINT ATTENTION MELALUI INTERVENSI JASPER PADA ANAK AUTIS KELAS IV DI SLB NEGERI 1 GOWA - Nirmalasari; Usman; Meidina, Tatiana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The problem studied in this study is the ability of joint attention in autistic students which is still very limited, characterized by low ability to respond and initiate joint attention. The purpose of this study is to determine the improvement of joint attention ability through the application of JASPER intervention in autistic students in grade IV. This research approach is a quantitative approach with a descriptive type of research that focuses on changes in ability before and after the intervention is given. The subject of this study is a fourth-grade autistic student with the initials GAN who has a very limited joint attention ability. The data collection technique used is a performance test adjusted to the joint attention indicator. Data analysis was carried out by comparing the test results before and after the implementation of the intervention, describing the test results before and after the implementation of the intervention. The conclusions of this study are 1) the ability of joint attention in autistic students in grade IV before the implementation of JASPER intervention is in the less category, 2) the ability of joint attention in autistic students in grade IV after the implementation of JASPER intervention is in the good category, 3) there is an increase in the ability of joint attention in autistic students in grade IV through the implementation of JASPER intervention from the less category to the good category. This study shows that the JASPER intervention is effective in improving the social interaction skills of autistic children.